Translanguaging and culturally sustaining pedagogies: A mutually dependent relationship? - Beiler, Ingrid Rodrick; Villacañas de Castro, Luis S. (Foreign language annals, 2025)
Translanguaging has increasingly been embraced in equity‐oriented research on foreign language teaching, yet with variable engagement with complex models of culture. In this article, we investigate the nexus of translanguaging and culturally sustaining pedagogies (CSP) as one response to this shortcoming. Extending previous research theoretically and contextually, our comparative case‐to‐case synthesis examines this nexus in English foreign language (EFL) teaching through ethnographic and participatory methods with students belonging to historically oppressed peoples in Europe, including Indigenous Sámi (Norway) and Roma (Spain) students, respectively. In the Norwegian case, student translanguaging demonstrated possibilities to shift English teaching toward CSP in a setting where such pedagogical practices were largely absent. In the Spanish case, the creativity favored by pedagogical translanguaging became essential for the students to expand their cultural perspectives and grow through English in an extracurricular implementation of CSP. Together, these cases demonstrate the mutual dependence of CSP and translanguaging.